Performance of zinc borate-treated oriented structural straw board against mold fungi, decay fungi, and termites – A preliminary trial - Han, Guangping; Cheng, Wanli; Manning, Mark; Eloy, Pierre (Bioresources, 2012)
The performance of zinc borate (ZB)-treated oriented structural straw board (OSSB) against mold fungi, decay fungi, and termites was examined in standard laboratory evaluations. OSSB was fabricated with split wheat straw strands and diphenylmethane diisocyante (pMDI) resin. The ZB was added during panel manufacture to achieve preservative levels (wt.%) of 1.0%, 1.5%, 2.0%, and 3.0%. It was observed that after a four-week exposure to mold fungi all samples had some mold coverage, but the coverage on the ZB-treated samples was significantly lighter compared to the untreated OSSB. Decay test showed that the weight losses of ZB-treated OSSB blocks at 1.0% and 1.5% levels were significantly reduced compared to the untreated OSSB and solid wood controls, indicating superior performance of ZB-treated OSSB against decay fungi. The termite mortality indicated that none of the termites were alive at the conclusion of the test for ZB-treated OSSB. The results from these specific laboratory studies demonstrated that ZB retentions of 1.5% and greater provide performance against decay fungi and termites for OSSB panels. In addition, untreated OSSB has high susceptibility to mold due to the chemical features of wheat straw and incomplete removal of kernels.